Extracellular Vesicles and Plant-Derived Vesicles in Cancer: From Mechanisms to Clinical Translation - Shery Jacob; Namitha Raichel Varkey; Sai H. S. Boddu; Jigar N. Shah; Ibrahim Mustafa Abdi; Rekha Rao (Pharmaceutics, 2026)
Extracellular vesicles (EVs) are naturally occurring nanoscale carriers that have gained attention as next-generation platforms for diagnostics, site-specific drug delivery, and tissue engineering owing to their high biocompatibility, minimal immunogenicity, and capacity to transport diverse bioactive cargo across biological barriers. This review discusses the classification, biogenesis, molecular constituents, and therapeutic properties of the major EV subtypes such as exosomes, microvesicles, and apoptotic bodies. It also highlights recent advances in EV engineering for cancer treatment, emphasizing immune modulation and targeted therapeutic delivery. Particular attention is given to plant-derived EVs, which have shown promise as scalable, low-toxicity nanotherapeutics with inherent bioactivity and effective drug delivery potential. Selected preclinical studies, recent patents, and ongoing clinical trials are also summarized, providing an up-to-date perspective on the clinical translation of EV-based technologies. Current challenges in EV isolation, characterization, scalable manufacturing, cargo loading, standardization, and regulatory approval, along with future directions for clinical translation, are summarized. Collectively, this review summarizes the growing applicability of EVs as next-generation platforms for precision medicine, targeted drug delivery, and regenerative therapies while identifying the major obstacles that must be addressed to facilitate their successful clinical translation.